Mitral Regurgitation in the High-Risk Patient: Integrating an Expanding Armamentarium of Transcatheter Devices Into the Treatment Algorithm. Issue 6 (9th August 2021) - Basman, Craig; Johnson, Joel; Pirelli, Luigi; Patel, Nirav C.; Reimers, Carl; Singh, Varinder P.; Scheinerman, S. Jacob; Kliger, Chad A.
Abstract : Over the last decade, multiple transcatheter mitral valve repair and replacement strategies have emerged, yet there is only 1 US Food and Drug Administration approved device, the MitraClip (Abbott Vascular, Inc., Santa Clara, CA). Current guidelines support the use of the MitraClip in high or prohibitive surgical risk patients, but there are many patients that are not anatomically suited for the device. This review article discusses the approach to degenerative and functional mitral regurgitation in the high-prohibitive risk patient, how to choose transcatheter treatment options (both approved and investigational), and potential management for therapy failure.